The Influence of Work Discipline and Professionalism on the Quality of Public Services at the Makassar City Employment Service - Jumaini; Asriati; Syarifuddin Sulaiman (Pustaka Digital Indonesia, 2024)
This research is a quantitative study aimed at determining the impact of work discipline and professionalism on the quality of public services at the Makassar City Manpower Office. The research employed quantitative analysis, utilizing observation, data collection through questionnaires with 53 respondents, as well as validation and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings revealed that the t-test results for work discipline indicated a significant value of 0.047 (less than 0.05) and a t-count value of 2.034, which is greater than the t-table value of 2.010. This signifies a positive and significant effect of work discipline on the quality of public services. Similarly, professionalism demonstrated a significant value of 0.001 (less than 0.05) and a t-count value of 4.728, which exceeds the t-table value of 2.010, indicating a positive and significant influence of professionalism on the quality of public services. Based on the research findings from data collection, management, and analysis, it can be concluded that both work discipline and professionalism have a positive and significant effect on the quality of public services at the Makassar City Manpower Office.